A Small Peak in the Swarm‐LP Plasma Density Data at the Dayside Dip Equator. Issue 7 (7th July 2022) - Song, Hosub; Park, Jaeheung; Buchert, Stephan; Jin, Yaqi; Chao, Chi Kuang; Lee, Jaejin; Yi, Yu
Abstract: In this paper, we statistically investigate an artifact in Langmuir Probe (LP) observations of Swarm satellites. A small peak of electron density ( N e ) is frequently found in the Swarm data around the dayside dip equator. On the contrary, they appear in neither the Total Electron Content data of the Swarm/Global Positioning System Receivers nor COSMIC‐2 in‐situ measurements at similar altitudes but with low orbit inclination. Arguably, this peak does not represent natural ionospheric irregularities but is likely to result from artifacts. The phenomena are found regardless of the season, solar activity, and the velocity direction of the satellite (ascending and descending). They predominantly occur when the magnetic declination is close to zero, that is, when the Swarm ram direction and the Earth's magnetic field are aligned under sunlight. Hence, we attribute the phenomenon to intensified secondary electrons escape when the geomagnetic field lines are normal to conducting surfaces that emit secondary electrons. Since the magnitude of the artifact is only a few percent of the large‐scale background, it does not have a serious impact on the value of the Swarm/LP data in scientific research. Nevertheless, future efforts to determine the exact cause of the artifacts will contribute to improving the reliability and quality of plasma density and temperature measured by Swarm/LP. Plain Language Summary: In this paper, we statistically investigate artifacts found in Langmuir Probe (LP) observations of Swarm satellites and search for their possible causes. LP is an instrument that measures the density and temperature of charged particles (so‐called "plasma") around the satellite. Unexpectedly, small peaks of plasma density often occur around the dayside dip equator in the Swarm/LP data, while they are not at all observed in other similar equipment, such as Swarm Global Positioning System Receivers or COSMIC‐2 satellites' ion probes at similar altitudes. For this reason, we deem this peak an artifact. This phenomenon occurs in all seasons, solar activity, and satellite movement directions. But, it predominantly appears when the ram direction of Swarm is nearly aligned with the Earth's magnetic field under sunlight. Hence, we consider that it originates from enhanced secondary electrons escape under a particular magnetic field configuration. The artifacts do not have a deleterious impact on scientific research because they are only a few percent of the background. However, efforts to determine the exact cause of artifacts are warranted for improving the reliability and quality of LP data. Key Points: Swarm encounters peaks of electron density at the dayside dip equator under zero magnetic declination, which is arguably an artifact The artifacts occur for all seasons and solar activity, and for both ascending/descending We suggest that the artifacts are associated with enhanced secondary electrons escape under favorable magnetic field configurations